THE PLACE OF ADVERBS IN THE UZBEK LANGUAGE AND THEIR STATUS AS A PART OF SPEECH - Badikova Oysuluv Gapirovna (Scholar Express Journal, 2023)
The article is devoted to study adverbs in non-related languages, the functions of the adverb in the sentence and their classification in the Uzbek language.
Keywords: adverb; Uzbek; classification